Size effect of flake Ti powders on the mechanical properties in graphene nanoflakes/Ti fabricated by flake powder metallurgy. (August 2019) - Mu, X.N.; Cai, H.N.; Zhang, H.M.; Fan, Q.B.; Wang, F.C.; Cheng, X.W.; Zhang, Z.H.; Li, J.B.; Jiao, X.L.; Ge, Y.X.; Chang, S.; Liu, L.; et al.
Abstract: The effect of the size of the flake Ti powders on fabricating graphene nanoflakes (GNFs)/Ti composites were investigated in this work. By this, the flake Ti powders of various size were produced via the flake powder metallurgy methods. The GNFs were tightly inserted into the flake Ti powders during high energy ball milling (HEBM) process. Raw spherical Ti powders (45 μm) with 4.34 deformation degree exhibit the best GNFs distribution on boundaries and in the interior of grains. Thus, after a short time heat treatment, the exceptional network-structural GNFs/Flake Ti properties were achieved with a good ductility and a superior compressive strength of ∼2.8 GPa. It was demonstrated that the excellent properties were mainly attributed to the proper combination of special distribution status and effective load transfer ability of titanium carbide interface. The results might provide new insights for designing advanced GNFs/Fake Ti composites with simultaneously high strength and ductility.